2008
DOI: 10.1007/s00040-008-1031-y
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the hormone-producing glands in the damp-wood termite Hodotermopsis sjostedti (Isoptera, Termopsidae): A focus on soldier differentiation

Abstract: Caste differentiation in termites depends on complex hormonal changes during postembryonic development. Juvenile hormone (JH) is a central player in this process. The present study examined histological changes in the main hormone-producing endocrine glands, the corpora allata and molt glands, in the Japanese dampwood termite Hodotermopsis sjostedti. We focused on the soldier caste differentiation pathway, which can be induced artificially using an analogue of JH. The corpora allata exhibited volumetric change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The present study clearly showed that caste‐specific morphogenesis (especially soldier cuticular pigmentation) requires 20E signaling gene expression changes as well as JH activity. In the damp‐wood termite Hodotermopsis sjostedti , hypertrophy of the prothoracic gland was observed in presoldiers . We suggest that, as well as EcR activity, 20E synthesis level changes may also be involved in the soldier‐specific cuticular tanning.…”
Section: Resultsmentioning
confidence: 81%
“…The present study clearly showed that caste‐specific morphogenesis (especially soldier cuticular pigmentation) requires 20E signaling gene expression changes as well as JH activity. In the damp‐wood termite Hodotermopsis sjostedti , hypertrophy of the prothoracic gland was observed in presoldiers . We suggest that, as well as EcR activity, 20E synthesis level changes may also be involved in the soldier‐specific cuticular tanning.…”
Section: Resultsmentioning
confidence: 81%
“…In termite caste differentiation, it has long been known that JH plays a critical role (Nijhout and Wheeler, ), and in H. sjostedti , JHA application induces growth of the corpora allata around Day 7 (Cornette et al, ). Our results show that IIS signaling was increased by JHA application, suggesting that the IIS pathway may also act downstream of JH.…”
Section: Discussionmentioning
confidence: 99%
“…3F). A histological study has shown that the prothoracic glands undergo growth at Day 7, prior to the presoldier molt (Cornette et al, 2008a). Recent evidence for a link between the IIS pathway and ecdysone action in determining body size (Caldwell et al, 2005;Colombani et al, 2005;Mirth et al, 2005) suggests that IIS may accelerate soldier differentiation by triggering prothoracic gland activity.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords Social insects · Caste differentiation · Gene expression · CYP15 · JHAMT * Kiyoto Maekawa kmaekawa@sci.u-toyama.ac.jp 1 Graduate School of Science and Engineering, University of Toyama, 3190 Gofuku, Toyama 930-8555, Japan changes were identified (e.g., Cornette et al 2008bCornette et al , 2013Koshikawa et al 2005;Masuoka et al 2013;Toga et al 2012Toga et al , 2013Watanabe and Maekawa 2012). However, it is still unknown when the genes involved in JH biosynthesis are activated and/or the JH titer increases during soldier differentiation under natural conditions.…”
Section: Introductionmentioning
confidence: 98%